A MULTIMODAL DISCOURSE ANALYSIS OF “WILLOW” MUSIC VIDEO BY TAYLOR SWIFT - Ni Made Dwi Utari Pusparini (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2025)
ABSTRACT There are many social platform that used as a place for funneling a music video, one of the biggest media platform is Youtube. Youtube supports attractive visualization through music video, song, and even text. Willow music video by Taylor Swift is one of music video that has unique multimodality aspect. The researcher used qualitative method and the multimodal discourse as an approach of this study.  The researcher used multimodal discourse analysis as the analysis method which examine textual communication, include images, symbols, as well as nonverbal communication like body language. To collected the data by multiple processes such as, observation, note-taking, and documentation. Primary and secondary data are the two categories of sources used in this study. Music video with entitled by “Willow” is considered as primary data and “Willow” lyric song as the secondary data. After collecting the data, the researcher analyzed it by some stages of the data, such as, analyzing the visual, audio, gesture and linguistic to make a note of the finding and concluding the results. The results of this research Willow music video clip shows various multimodality aspects that are interrelated each other. The Willow song by Taylor Swift conveys a message of love life.